Targeting Autophagy in Thyroid Cancer: EMT, Apoptosis, and Cancer Stem Cells - Holm, Tammy M.; Yeo, Syn; Turner, Kevin M.; Guan, Jun-Lin (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a highly conserved recycling process through which cellular homeostasis is achieved and maintained. With respect to cancer biology, autophagy acts as a double-edged sword supporting tumor cells during times of metabolic and therapeutic stress, while also inhibiting tumor development by promoting genomic stability. Accumulating evidence suggests that autophagy plays a role in thyroid cancer, acting to promote tumor cell viability and metastatic disease vis-à-vis supporting epithelial-to-mesenchymal transition (EMT), preventing tumor cell death, and maintenance of cancer stem cells (CSCs). Several studies have demonstrated that autophagy inhibitors may augment the anti-cancer effects of known thyroid cancer therapies. Autophagy modulation has become an attractive target for improving outcomes in thyroid cancer. This review aims to provide a comprehensive picture of the current knowledge regarding the role of autophagy in thyroid cancer, focusing on the potential mechanism(s) through which inhibition of autophagy may enhance cancer therapy and outcomes.